The influence of galaxy environment on the stellar initial mass function of early-type galaxies - Rosani, Giulio; Pasquali, Anna (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. In this paper, we investigate whether the stellar initial mass function (IMF) of early-type galaxies depends on their host environment. To this purpo